2016
DOI: 10.1016/j.ijid.2016.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis in treatment-naïve HIV-infected and HIV/HBV co-infected patients: Zambia and Switzerland compared

Abstract: Objective To examine the association between HBV infection and liver fibrosis in HIV-infected patients in Zambia and Switzerland. Design and Methods We included HIV-infected adults starting antiretroviral therapy in two clinics in Zambia and Switzerland. Liver fibrosis was evaluated using the AST-to-Platelet-Ratio Index (APRI), with a ratio >1.5 defining significant fibrosis and >2.0 cirrhosis. The association between HBsAg-positivity, HBV replication and liver fibrosis was examined using logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…Obviously, these studies observed varied prevalence of liver fibrosis among HIV patients, which are mostly attributable to different sources and characteristics of the study participants. Nevertheless, all the aforementioned studies including the present study reported that liver fibrosis was more prevalent among patients with HBV and/or HCV coinfection than those with HIV monoinfection, which is also consistent with findings from other countries (22,(29)(30)(31).…”
Section: Discussionsupporting
confidence: 93%
“…Obviously, these studies observed varied prevalence of liver fibrosis among HIV patients, which are mostly attributable to different sources and characteristics of the study participants. Nevertheless, all the aforementioned studies including the present study reported that liver fibrosis was more prevalent among patients with HBV and/or HCV coinfection than those with HIV monoinfection, which is also consistent with findings from other countries (22,(29)(30)(31).…”
Section: Discussionsupporting
confidence: 93%
“…The relationship of active viral replication with fibrosis implicates active antigen-specific anti-viral responses as being important to pathogenesis of liver fibrosis. Viral replication as the driver of liver fibrosis has been reported among treatment-naïve HBV/HIV co-infected patients in Zambia and Switzerland [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that this practice is influenced by a greater perceived risk of developing inflammatory liver conditions in coinfected patients. 49 Amongst the coinfected group, who were more likely to have undergone assessment, 10% of individuals were nevertheless still lacking elastography results. We were unable to determine specific treatment duration for a proportion of the patients studied, adding to uncertainty about exposure to antiviral therapy in HBV and HBV/HIV infected groups.…”
Section: Caveats and Limitationsmentioning
confidence: 99%